PERSEPSI MAHASISWA TEKNOLOGI PENDIDIKAN SEMESTER 2 KELAS B UNIVERSITAS MUHAMMADIYAH BONE TERHADAP PENGGUNAAN GEMINI SEBAGAI MEDIA PEMBELAJARAN INTERAKTIF UNTUK MENINGKATKAN MOTIVASI BELAJAR - Noviandani, Nabila; Ahmad Nurul Ihsan; Jusman (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The rapid development of artificial intelligence has encouraged the integration of AI-based applications into higher education learning. One of the applications widely used by students is Google Gemini, which functions as an interactive learning medium capable of facilitating access to information, assisting in understanding learning materials, and supporting academic assignments. This study aimed to explore students' perceptions of the use of Google Gemini as an interactive learning medium in improving learning motivation, identify the obstacles encountered during its use, and describe the strategies employed by students to overcome these obstacles. This research employed a qualitative approach with a phenomenological design. The participants consisted of 35 second-semester students of Class B in the Educational Technology Study Program at Universitas Muhammadiyah Bone. Data were collected through interviews, observations, questionnaires, and documentation, while data analysis followed the Miles and Huberman interactive model involving data collection, data reduction, data display, and conclusion drawing. The findings indicate that students generally have positive perceptions of Google Gemini because it is easy to use, provides quick access to information, assists in understanding course materials, and enhances learning motivation through increased curiosity, confidence, and active participation. However, several challenges remain, including unstable internet connectivity and limited understanding of some application features. Students addressed these challenges by seeking additional learning resources, discussing with peers, and improving their digital literacy. The study concludes that Google Gemini has considerable potential to support interactive learning and foster students' learning motivation when accompanied by appropriate digital competence.